STUDI TENTANG KAIN SONGKET DI STUDIO SONGKET SUMATERA LOOM KECAMATAN AMPEK ANGKEK KABUPATEN AGAM (STUDI KASUS) - Astuti, Fitri Jaya; Nazar, Ernawati; Yasnidawati, Yasnidawati (Journal of Home Economics and Tourism, 2015)
Studio Songket Sumatra Loom able to revitalize songket songket-old, and capable of producing quality songket, also has its own characteristic songket, both in terms of yarn, color, pattern and shape of the resulting product. The purpose of this research is to describe the history of songket, yarn types, colors, patterns, and shapes of products in Studio Songket Sumatra Loom. The method used in this research is a case study with a qualitative approach. The technique of collecting data through observation, interviews and documentation. Collecting data using primary and secondary sources. The data analysis is done by using interactive analysis relating to the subject matter that is the data reduction, data display, and conclusion end. Results of the research: History Loom Studio Songket Sumatra, Sumatra leader Loom is Bernhard Bart. Bernhard was interested in the motives and complexity songket making techniques and finally Bernhard decided to open Studio Songket in 2005 which was formerly Erika Rianti, in 2013 the name changed to the name Loom Studio Songket Sumatra. Type of yarn used is silk threads and yarns macau (gold and silver) .warna used yellow gold, silver, red, black, pink, blue, purple, brown, green, orange, and gray. Has 22 motifs that resemble plants, animals, geometric shapes and custom words. The shape of the resulting product is complete the form salendang custom clothing, gloves, belts, sisamping, deta, dalamak and souvenirs in the form of wall hangings.Kata kunci: studi kasus, kain songket, ampek angkek